Use of natural resources from Southern Brazil as a strategy to mitigate fungal contamination. Issue 2 (19th January 2021) - Badiale Furlong, Eliana; Badiale Furlong, Vitor; Kupski, Larine; Scaglioni, Priscila Tessmer; Denardi de Souza, Taiana; Christ-Ribeiro, Anelise
Abstract: Contamination of food by fungi can result in changes in sensory characteristics, as well as rapid reduction in quality and consequently the infeasibility of using contaminated material. In addition, contamination can pose a danger to public health, as in addition to decreasing the availability of nutrients, some fungal species can produce toxic substances. Much research has explored the use of natural resources to prevent or mitigate microbial contamination. Recovery of chemicals from many families from plants and microorganisms has been evaluated. Phenolic compounds are the most studied class on the premise that they have the capacity to inhibit endogenous and exogenous biological degradation processes. In this manuscript, we intend to emphasize the biochemical and experimental evidence of the phenolic compounds present in natural resources from the South of Brazil that have potential to be used in strategies to mitigate the consequences of fungal contamination. The crude phenolic extracts from natural resources (plant portion and microorganisms) of the Southern Brazilian region should be better exploited, to propose strategies to scale up their application in food industries because they have demonstrated an ability to inhibit fungal development without promoting stress and consequent mycotoxin production.